Strategi Dinas Tenaga Kerja dalam Meningkatkan Kompetensi dan Akses Pelatihan Bagi Calon Tenaga Kerja di Kabupaten Ciamis - Galih Purnama; Arie Budiawan; Irfan Nursetiawan (Lembaga Pengkajian Dan Pengembangan Sumberdaya Pembangunan (lppsp), 2024)
This study is motivated by the suboptimal strategies of the Ciamis Regency Manpower Office in enhancing the competence and access to training for prospective workers in Ciamis Regency. The main issues include a lack of comprehensive efforts, incomplete and outdated data on labor market needs, and budget constraints. The aim of this research is to examine the efforts of the Manpower Office in improving the competence and training access for prospective workers in Ciamis Regency. This study employs a descriptive qualitative approach through observation, interviews, and documentation. The results indicate that out of the three strategy dimensions (formulation, implementation, evaluation), two are not yet fully effective. In the formulation dimension, there is a need to improve training accessibility for residents in remote or underdeveloped areas. The implementation of training strategies is still too general and lacks specificity, requiring diversification to cover various relevant industry sectors. Evaluation is conducted through regular internal meetings to monitor effectiveness and adjust strategies accordingly. Efforts made include competency-based training that covers the development of soft skills and personal attributes of prospective workers, as well as guiding participants to become entrepreneurs with small initial capital. This research utilizes Sedarmayanti's grand theory of strategic management, which includes Strategy Formulation, Implementation, and Evaluation.